HELP: star formation as a function of galaxy environment with Herschel - Duivenvoorden, S; Oliver, S; Buat, V; Darvish, B; Efstathiou, A; Farrah, D; Griffin, M; Hurley, P; Ibar, E; Jarvis, M; Papadopoulos, A; Sargent, M; et al. (Oxford University Press, 2016)
The Herschel Extragalactic Legacy Project (HELP) brings together a vast range of data frommany astronomical observatories. Its main focus is on the Herschel data, which maps dustobscured star formation over 1300 deg 2 . With this unprecedented combination of data sets, it is possible to investigate how the star formation versus stellar mass relation (main sequence)of star-forming galaxies depends on environment. In this pilot study, we explore this question within 0.1 < z < 3.2 using data in the COSMOS field. We estimate the local environment from a smoothed galaxy density field using the full photometric redshift probability distribution. We estimate star formation rates by stacking the SPIRE data from the Herschel Multi-tiered Extragalactic Survey. Our analysis rules out the hypothesis that the main sequence for starforming systems is independent of environment at 1.5 < z < 2, while a simple model in which the mean specific star formation rate declines with increasing environmental density gives a better description. However, we cannot exclude a simple hypothesis in which the main sequence for star-forming systems is independent of environment at z < 1.5 and z > 2. We also estimate the evolution of the star formation rate density in the COSMOS field, and our results are consistent with previous measurements at z < 1.5 and z > 2 but we find a 1.4 +0.3 -0.2 times higher peak value of the star formation rate density at z ~ 1.9.